Flt3 ligand-treated neonatal mice have increased innate immunity against intracellular pathogens and efficiently control virus infections - Vollstedt, Sabine; Franchini, Marco; Hefti, Hans P; Odermatt, Bernhard; O'Keeffe, Meredith; Alber, Gottfried; Glanzmann, Bettina; Riesen, Matthias; Ackermann, Mathias; Suter, Mark (The Journal of experimental medicine, 2003)
Flt-3 ligand (FL), a hematopoetic growth factor, increases the number of dendritic cells (DCs), B cells, and natural killer cells in adult mice but the effect in neonates was unknown. We show that FL treatment of newborn mice induced a >100-fold increase in the innate resistance against infection with herpes simplex virus type 1 and Listeria monocytogenes. This resistance required interferon (IFN)-alpha/beta for viral and interleukin (IL)-12 for bacterial infections. Long-term survival after viral but not bacterial infection was increased approximately 100-fold by FL treatment. After treatment, CD11c(+)/major histocompatibility complex type II(+) and CD11c(+)/B220(+) DC lineage cells were the only cell populations increased in the spleen, liver, peritoneum, and skin. DC induction was independent of IFNs, IL-2, -4, -7, -9, -15, and mature T and B cells. The data suggest that FL increases the number of DCs in neonates and possibly in other immune-compromised individuals, which in turn improves IFN-alpha/beta- and IL-12-associated immune responses.